Correlation Between Angiotensin Receptor Type 1 Polymorphisms and Atherosclerotic Cerebral Infarction Risk - Chen L; Wang Y; Wang Y; Huang S; Wu Z; He J; Zhong W; Zhao B; Ma G; Li Y (Dove Medical Press, 2022)
Linfa Chen,1,2,* Ying Wang,1,3,* Yajun Wang,4,* Shaoting Huang,1,3 Zhaochun Wu,1,3 Jiawen He,1,3 Wangtao Zhong,3 Bin Zhao,1,3 Guoda Ma,1,4 You Li1,5 1Guangdong Key Laboratory of Age-Related Cardiac and Cerebral Diseases, Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, 524001, People's Republic of China; 2Department of Neurology, Huizhou Third People's Hospital, Guangzhou Medical University, Huizhou, Guangdong, 516002, People's Republic of China; 3Department of Neurology, Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, 524001, People's Republic of China; 4Maternal and Children's Health Research Institute, Shunde Maternal and Children's Hospital, Guangdong Medical University, Shunde, Guangdong, 528300, People's Republic of China; 5Institute of Neurology, Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, 524001, People's Republic of China*These authors contributed equally to this workCorrespondence: You Li, Guangdong Key Laboratory of Age-Related Cardiac and Cerebral Diseases, Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, 524001, People's Republic of China, Email youli805@163.com Guoda Ma, Maternal and Children's Health Research Institute, Shunde Maternal and Children's Hospital, Guangdong Medical University, Shunde, Guangdong, 528300, People's Republic of China, Email sihan1107@126.comBackground: Emerging evidences suggest that the angiotensin receptor type 1 (AT1R) contributes heavily to the pathogenesis of atherosclerotic cerebral infarction (ACI). Herein, we examined a potential link between AT1R gene polymorphisms and ACI risk among a Southern Han Chinese population.Methods: The rs3772616, rs275645, and rs377262 AT1R polymorphisms were genotyped in 689 ACI patients and 712 healthy controls, using the iMLDR-TM assay.Results: The genotypic and allelic frequencies of AT1R rs3772616 differed tremendously between ACI patients and healthy controls, and the rs3772616 T allele is a risk allele for ACI. However, the rs275645 and rs377262 allelic and genotypic frequency distributions were comparable between ACI patients and controls. In addition, the G-T-T haplotype was linked to an enhanced risk of ACI. We, next, classified our study subjects based on environmental factors and revealed that the rs3772616 T allele was strongly associated with an elevated ACI risk in males, hypertensive individuals, and those over 65 years old. In addition, we observed a marked link between the rs3772616 T allele and enhanced AT1R levels.Conclusion: Based on our research, there is a strong correlation between the AT1R rs3772616 polymorphism and enhanced ACI risk. Hence, the AT1R rs3772616 polymorphism can serve as a potential therapeutic target and bioindicator for ACI development.Keywords: angiotensin receptor type 1, polymorphism, atherosclerotic cerebral infarction, case-control